Praktik Psikoterapi Mengenai Pelatihan Keterampilan Terapi Kelompok Perilaku Dialektika di Indonesia: Pengembangan Modul dalam Bahasa Indonesia - Natalia Dewi Wardani; Maria Immaculata Widiastuti; Aris Sudiyanto; Hardian Hardian; Hertanto Wahyu Subagio; Dodik Tugasworo; Gusti Ayu Maharatih; Petrin Redayani Lukman; Debree Septiawan; Rini Suprapti; Kezia Natalia Daniast Susilo; Diana Atmaja; Amalia Andansari Dewi (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2023)
Introduction: There is an increasing number of suicides in Indonesia. A high risk of suicide is often associated with borderline personality disorder (BPD). To address this issue, dialectical behavior therapy (DBT) has been specifically designed for patients with frequent suicidal behavior and BPD. This study aims to develop DBT skills modules in Indonesian language for groups therapy and implement in clinical practice.Methods: This research was conducted in three stages. Stage 1 involved preparing the DBT skills module for 13 weeks, including the adding of TIPP (Temperature, Intense exercise, Paced Breathing, Paired Muscle Relaxation) distress tolerance skills and chain analysis. Stage 2 focused on module validation using face validity and content validity assessment conducted by two psychotherapy consultants. Stage 3 involved modules trials, both of whom had completed DBT training, practicing the prepared modules with two groups of 10 patients.Result: The face validity scores from the two experts for the DBT module on BPD in Indonesian was 3.188, indicating a high level of correctness. The content validity results from the two experts for the DBT module on BPD in Indonesian language were 84.06, indicating that almost everything was done correctly. After practicing DBT group skills training, two psychotherapists achieved a very good interrater score of 0.969 (p=0.003; 95% CI 0.746-0.997).Conclusion: Based on the face validity and content validity scores by the two experts, it was concluded that the DBT module for BPD in Indonesian language is suitable for use in clinical services.